2022
DOI: 10.1186/s11671-022-03675-7
|View full text |Cite
|
Sign up to set email alerts
|

Compact and Scalable Large Vortex Array Generation Using Azocarbazole Polymer and Digital Hologram Printing Technique

Abstract: An integrated device capable of generating large number of multiplexed optical vortex beams with arbitrary topological charge is considered as one of the crucial requirement for driving information photonics forward. Here we report a simple method for simultaneous generation of 100 multiplexed optical vortex beams from a polymer film of size 1 mm2 and thickness of 30 μm. This is achieved through a combination of computer-generated holography, digital hologram printing and photoisomeric polymers. When the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A 10× demagnifying lens arrangement transfers the intensity pattern passing through the PBS onto the sample as refractive index modulation through a process called photoinduced birefringence. The sample is mounted on a high-precision 3-axis motion stage for accurate position of the sample w.r.t the illuminating beam (for more details about the printing setup, one may refer to Jackin et al [ 19 ]). The laser power at the sample plane is measured to be 32 mW/mm and the recording is performed with a 5 s exposure.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10× demagnifying lens arrangement transfers the intensity pattern passing through the PBS onto the sample as refractive index modulation through a process called photoinduced birefringence. The sample is mounted on a high-precision 3-axis motion stage for accurate position of the sample w.r.t the illuminating beam (for more details about the printing setup, one may refer to Jackin et al [ 19 ]). The laser power at the sample plane is measured to be 32 mW/mm and the recording is performed with a 5 s exposure.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…All the existing methods, tools and techniques for generating Ince–Gaussian and other similar structural beams require a bulky system assembled on an optical bench or a complex fabrication method (e.g., metamaterials) [ 18 ]. We have recently shown that compact vortex beam generators can be realized by using azocarbazole CGH [ 19 ], which is simple and compact. In this paper, we further extend the method to incorporate the more general IG beams and their generation.…”
Section: Introductionmentioning
confidence: 99%
“…The multiplexing techniques are employed on the azo-carbazole polymer film synthesized in our lab, which shows very high diffraction efficiency and long retention time for polarization holograms. [22][23][24][25][26][27] The hologram is recorded at 20°angle (angle between object and reference beam), and the recorded hologram falls in the category of Bragg Hologram.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, holography is expected to be used not only for applications related to images but also for lighting, data storage, information communication, and medical field applications. [1][2][3][4][5][6] In recent years, numerous studies have been conducted on materials that can be adapted to produce dynamic holograms, which are rewritable holograms that improve upon static holograms. Typical materials for updatable holograms include azobenzene molecules in a polymer matrix, [7][8][9] liquid crystals, 10,11 polymer liquid crystals, [12][13][14][15][16] and photorefractive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, holography is expected to be used not only for applications related to images but also for lighting, data storage, information communication, and medical field applications. 1–6…”
Section: Introductionmentioning
confidence: 99%